Broad tapeworms (Diphyllobothriidae), parasites of wildlife and humans: Recent progress and future challenges - Scholz, Tomáš; Kuchta, Roman; Brabec, Jan (International journal for parasitology. Parasites and wildlife, 2019)
Tapeworms of the family Diphyllobothriidae, commonly known as broad tapeworms, are predominantly large-bodied parasites of wildlife capable of infecting humans as their natural or accidental host. Diphyllobothriosis caused by adults of the genera Dibothriocephalus, Adenocephalus and Diphyllobothrium is usually not a life-threatening disease. Sparganosis, in contrast, is caused by larvae (plerocercoids) of species of Spirometra and can have serious health consequences, exceptionally leading to host's death in the case of generalised sparganosis caused by 'Sparganum proliferum'. While most of the definitive wildlife hosts of broad tapeworms are recruited from marine and terrestrial mammal taxa (mainly carnivores and cetaceans), only a few diphyllobothriideans mature in fish-eating birds. In this review, we provide an overview the recent progress in our understanding of the diversity, phylogenetic relationships and distribution of broad tapeworms achieved over the last decade and outline the prospects of future research. The multigene family-wide phylogeny of the order published in 2017 allowed to propose an updated classification of the group, including new generic assignment of the most important causative agents of human diphyllobothriosis, i.e., Dibothriocephalus latus and D. nihonkaiensis. Genomic data of selected representatives have also begun to accumulate, promising future developments in understanding the biology of this particular group of parasites. The list of nominal species of taxonomically most complicated genus Spirometra as well as host-parasite list of 37 species of broad tapeworms parasitising marine mammals (pinnipeds and cetaceans) are also provided.